Problemy rozwoju lokalnego na przykładzie Polsko-Czeskiej Izby Przemysłowo-Handlowej - Adamczuk, Franciszek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
This article concerns problems of regional development on the Polish-Czech borderland. The role of the Polish-Czech Chamber of Commerce and Industry (PCZIPH) has been displayed as a local initiative, which is ranked as an endogenic factor (internal factor). The analysis is based on the origin data gathered by PCZIPH in Świdnica and by the General Consulate of Polish Republic in Prague. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 297-305